Synthesis and Characterization of New 1,2,4-Triazole Derivatives Form 2-Naphthol (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this work 1,2,4-triazole derivatives were synthesized from [4-(2-hydroxy naphthyl)diazenyl]benzoic acid [N1] then converted to  [4-(2-hydroxy naphthyl)diazenyl] benzoate [N2] which reacted with thiosemicarbazide and then cyclization by using sodium hydroxide. Then different alkyl halides like (methyl iodide, allyl chloride, proprgyl chloride and benzyl chloride) were added to[4-(2-hydroxy naphthyl)diazenyl]-4H-1,2,4-triazole-3-thiol [N4] that led to alkylation of thiol to afforded compounds [N5] – [N8]. These compounds were characterized by the following techniques: FT-IR, and 1H , 13C NMR spectroscopies, and elemental analysis C.H.N.S. The physical properties of prepared compounds were studied.